Properties of micro-nano carbon materials/hydrogenated nitrile rubber composites prepared by solution method - ZHENG Fang-yuan1， LI Shi-kun2， ZHANG Zeng2， LI Zai-feng2 (Hecheng xiangjiao gongye)
A series of hydrogenated nitrile rubber (HNBR)/carbon nanotubes (CNTs)/graphene (GE) composites were prepared using a solution mixing process, with CNTs and GE as additives. The effects of micro-nano carbon materials on the vulcanization characteristics, mechanical properties, and thermal-oxidative aging resistance of HNBR were investigated. The results indicated that the incorporation of micro-nano carbon materials prolonged the optimal vulcanization time of HNBR and increased the torque difference. The micro-nano carbon materials exhibited excellent modification effects on the HNBR matrix. Compared to the pure HNBR matrix, the composite with a GE to CNTs mass ratio of 1/2 showed a 23.9% increase in tensile strength and a 3.2 times improvement in tear resistance. Owing to the hyperconjugated structure of the micro-nano carbon materials, the aging resistance coefficient of the composite reached 5.2 times that of pure HNBR matrix after 24 h of aging at 180 ℃. Furthermore, the crosslinking density of the aged composite was two orders of magnitude lower than that of the matrix. Compared to the rubber matrix, the glass transition temperature and maximum thermal decomposition rate of HNBR composites shifted toward higher temperatures.